Iron-based modified biochar composite material as well as preparation method and application thereof
Biochar is prepared by pyrolyzing the rubber seed shell and loading it with nano zero-valent iron to form an iron-based modified biochar composite, which solves the problem of difficulty in removing chain latsulphin toxins in the prior art, and achieves efficient adsorption and removal effects.
Patent Information
- Application Number
- CN202411925030.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art is difficult to effectively remove the pollution of cylindrical toxins in the water environment, and there is little research on the adsorption removal technology combining biochar and nano zero-valent iron.
Biochar is prepared by pyrolyzing the rubber seed shell and loading nano zero-valent iron through conventional liquid phase reduction method to form an iron-based modified biochar composite material, changing its pore structure and surface functional groups, and improving the adsorption effect of cylindrical toxins.
It has achieved efficient adsorption and removal of lattice toxins, with large adsorption capacity and short time to achieve adsorption equilibrium. The surface functional groups and lattice toxins form stable compounds or complexes, which significantly improves the adsorption performance.
Smart Images

Figure CN119657079A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biochar materials, and in particular relates to an iron-based modified biochar composite material and a preparation method and application thereof. Background Art
[0002] Biochar is generally a type of highly aromatic solid product rich in carbon prepared by high-temperature pyrolysis. It is a low-cost, effectively dispersed and stable carbonaceous material. Because it has surface charge, porous structure and rich functional groups, it has a good adsorption and removal effect on pollutants. Rubber seeds are mainly composed of rubber seed shells and rubber seed kernels, of which the rubber seed shell accounts for about 30%-50% of the total weight of rubber seeds. It is rich in lignin, cellulose, hemicellulose, etc., and is easy to pyrolyze and carbonize. It is a very promising biochar raw material. my country's rubber planting has a high annual rubber seed yield and abundant available resources. However, the biochar prepared directly from rubber seeds has a simple structure, a small specific surface area, a small number and type of pore structure and surface functional groups, and a weak ability to adsorb and fix pollutants.
[0003] Nanozero-valent iron (nZVI) is an environmentally friendly material that has received extensive attention in the removal / stabilization of pollutants such as heavy metals in water and soil. Due to its micromagnetic properties and high reactivity, nZVI is very easy to agglomerate, which limits its application in pollution remediation.
[0004] Alternaria Toxins are a class of secondary metabolites produced by Alternaria fungi. This type of fungi is widely present in nature and can infect a variety of plants, including crops, thus affecting food safety and human health. Alternaria toxins mainly include but are not limited to the following: AOH (Altenuisol): AOH is one of the toxins produced by Alternaria fungi, which is mainly found on grains, fruits and vegetables. The toxic effect of AOH on the human body is mainly achieved by interfering with the structure and function of the cell membrane, which may cause cell damage or death. AME (Altenuene): AME is also another toxin produced by Alternaria fungi. Its chemical structure is similar to AOH and it also has potential cytotoxicity.
[0005] Currently, the impact of Alternaria toxin in the water environment has gradually attracted attention, but the technology for its removal is still lacking, and there are relatively few studies on the adsorption and removal technology and mechanism of the combination of biochar and nano-zero-valent iron.
[0006] Therefore, there is an urgent need for an iron-based modified biochar composite material specifically for the adsorption of Alternaria toxin. Summary of the invention
[0007] The purpose of the present invention is to provide an iron-based modified biochar composite material and a preparation method and application thereof.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] A method for preparing an iron-based modified biochar composite material comprises the following steps:
[0010] (1) Preparation of biochar: Rubber seed shells are crushed after impurities are removed, put into a ceramic crucible, covered with a lid, and pyrolyzed and carbonized in a muffle furnace. The heating rate is set to 5-10°C / min, the temperature is raised to 200-210°C, and the temperature is kept for 1-2 hours. Then, the temperature is raised to 440-460°C at a rate of 15-20°C / min, and the temperature is kept for 2-3 hours. After cooling, the rubber seed shells are ground through a 20-mesh sieve to obtain biochar;
[0011] (2) Preparation of nano-zero-valent iron modified biochar: FeSO4·6H2O and biochar were added to an ethanol aqueous solution to obtain a mixture, a surfactant was added, and after ultrasonication for 30-50 minutes, nitrogen was introduced to blow off the dissolved oxygen, and the mixture was reacted in a constant temperature oscillator at 25-27°C and 140-160 rpm for 24-26 hours. After the reaction, NaBH4 aqueous solution was added and stirred for 30-40 minutes; centrifugation was performed to obtain a solid, and the solid was washed and vacuum dried to obtain an iron-based modified biochar composite material.
[0012] Further, the temperature was increased to 450° C. at a rate of 17° C. / min.
[0013] The present invention uses rubber seed shells as raw materials to prepare biochar. Rubber seed shells are byproducts in the rubber seed processing process and are usually treated as waste. Converting them into biochar can realize the resource utilization of waste, reduce pollution to the environment, and increase the added value of the product, which is of great significance to environmental protection.
[0014] In the prior art, the carbonization process of biochar loaded with nano zero-valent iron mainly focuses on achieving the degree of dispersion of zero-valent iron, realizing embedded loading, making the load strength higher, and thus improving the adsorption effect. However, the adsorption effect of the composite material for adsorbing Alternaria toxin in the present invention is also related to the functional groups on the surface of biochar. The present invention can improve the removal effect of the prepared iron-based modified biochar composite material on Alternaria toxin through a specific carbonization procedure. After high-temperature carbonization, the rubber seed shell biochar becomes fragmented and has a smooth surface; when the surface of the biochar is loaded with nZVI, fine granular substances appear on the surface of the biochar, and its specific surface area and pore volume are both reduced, but the average pore size is slightly increased, mainly concentrated in the mesopore size. After nZVI is loaded on the biochar, it will enter the porous structure of the biochar, thereby changing the pore structure of the biochar, resulting in a decrease in the overall specific surface area and pore volume, and an increase in the average pore size. The nZVI-BC of the present invention can fix more AOH and AME toxins in a shorter time, has a larger adsorption capacity, and takes a shorter time to reach adsorption equilibrium. The adsorption performance is not reduced due to the reduction in specific surface area and pore volume, but is significantly improved. This shows that in the system of the present invention, van der Waals force and micropore filling are not the main mechanisms for nZVI-BC to adsorb such toxins. The present invention mainly achieves adsorption and removal by acting on functional groups such as hydroxyl groups on the surface of Alternaria toxin.
[0015] During the experiment, it was found that the heating program had a greater effect on the removal of Alternaria toxins by the iron-based modified biochar composite material. The heating program had a greater impact on the aromatization and formation of functional groups in the composite material. These oxygen-containing functional groups played a very important role in the adsorption of Alternaria toxins. In particular, the temperature heating rate after about 200°C had a greater impact on the performance. The heating effect was better at a rate of 15-20°C / min, and a good adsorption effect could be achieved for all four Alternaria toxins. During the pyrolysis process, the structure of the raw material changed with the temperature. When the temperature was from room temperature to about 200°C, the weight loss of the raw material was relatively slow, mainly because easily decomposable substances such as water and small molecular compounds would be released, which could promote the aromatization of rubber seed shell charcoal. When the temperature continued to rise, the weight loss of the raw material changed greatly, first decomposing rapidly, and then tending to ease. In this process, cellulose, hemicellulose and lignin in the raw material were dehydrated and depolymerized, producing solid charcoal, wood vinegar and synthesis gas.
[0016] During the experiment, it was found that in the process of preparing biochar using rubber seed shell as raw material, abundant oxygen-containing functional groups, such as carbonyl (C=O) and COC (ether) functional groups, were generated on the surface of biochar. These oxygen-containing functional groups played an important role in the adsorption of Alternaria toxin by biochar. Fig.12As shown, AOH and AME toxins contain abundant functional groups such as hydroxyl groups. Rubber seed shell charcoal can fix such Alternaria toxins through ligand exchange between functional groups, thereby achieving efficient removal of similar Alternaria toxins. Changing the heating rate during pyrolysis will have a greater impact on these oxygen-containing functional groups. The heating program of the present invention can promote the formation of these functional groups, thereby improving its adsorption effect on Alternaria toxins.
[0017] Furthermore, the surfactant is sodium dodecylbenzene sulfonate (SDBS).
[0018] In the process of preparing nano-zero-valent iron modified biochar, adding sodium dodecylbenzene sulfonate as a surfactant can improve the dispersion of nano-zero-valent iron on biochar. Because sodium dodecylbenzene sulfonate can inhibit the agglomeration of nanoparticles by providing additional electrostatic repulsion and steric hindrance, and improve dispersibility and stability, it can promote the loading of nZVI on biochar and make it more evenly distributed on the surface of biochar. The compatibility of biochar with nano-zero-valent iron, the surface properties and pore structure of biochar can affect the loading and dispersion of nano-zero-valent iron. The present invention selects suitable biochar raw materials and carbonization conditions, and through surface modification (surfactant modification), it can improve the surface activity and hydrophilicity of biochar and enhance the loading capacity of nano-zero-valent iron.
[0019] The 24-hour adsorption rate can be used to evaluate the maximum adsorption capacity of the composite material for the four Alternaria toxins, which is crucial for the design and optimization of water treatment systems. The maximum adsorption capacity determines the required material dosage and treatment cost. In the present invention, when the surfactant is sodium dodecylbenzene sulfonate, the 24-hour adsorption rate of the iron-based modified biochar composite material for Alternaria toxins is improved.
[0020] Furthermore, the weight ratio of FeSO4·7H2O and biochar is (23-26):10.
[0021] Further, the amount of ethanol aqueous solution added is 8-10 times the total weight of FeSO4·7H2O and biochar.
[0022] Furthermore, the volume ratio of ethanol to water in the ethanol aqueous solution is 1:(2-4).
[0023] Furthermore, the weight of the surfactant accounts for 0.05-0.06% of the weight of the mixture.
[0024] Further, a NaBH4 solution with a concentration of 1-1.2 mol / L was added at a flow rate of 1.4-1.6 mL / min using a peristaltic pump.
[0025] Furthermore, the molar ratio of NaBH4 and FeSO4·7H2O is (3-4):4.
[0026] Furthermore, the method of cleaning and vacuum drying is: first cleaning with ethanol for 3-4 times, then cleaning with water for 3-4 times, and vacuum drying for 12-15 hours.
[0027] The second aspect of the present invention provides an iron-based modified biochar composite material obtained by the preparation method.
[0028] The third aspect of the present invention provides the use of the iron-based modified biochar composite material in the adsorption of Alternaria toxin.
[0029] Furthermore, the Alternaria toxin includes one or more of Alternariol (AOH), Alternariol monomethylether (AME), Tenuazonic acid (TeA), and Tentoxin (TEN).
[0030] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0031] 1. The unique properties and structure of the biochar prepared by the present invention can react with Alternaria toxins, thereby achieving efficient removal of the four Alternaria toxins and reducing their harm to the environment and human health.
[0032] 2. The present invention uses rubber seed shell as raw material and prepares rubber seed shell biochar by pyrolysis and carbonization. By controlling the pyrolysis conditions, the prepared biochar has high adsorption performance for Alternaria toxins such as AOH and AME, and prepares nano zero-valent iron modified biochar nZVI-BC by a conventional liquid phase reduction method, which changes the physical and chemical properties of the final biochar. The pore size distribution is mainly concentrated in the mesopore size. nZVI-BC fixes more Alternaria toxins in a shorter time and has a larger adsorption capacity. The time to reach adsorption equilibrium is shorter, and the surface functional groups form more stable compounds or complexes with Alternaria toxins, thereby achieving efficient and stable adsorption and removal of Alternaria toxins.
[0033] 3. The present invention prepares environmentally friendly biochar by pyrolysis of rubber seed shells, thereby realizing resource utilization and reducing resource waste and environmental pollution. Combining biochar with nano zero-valent iron and using biochar as a carrier can solve the problem of easy oxidation and easy agglomeration of nano zero-valent iron, effectively improve the application of nano zero-valent iron, improve the effect of its practical application, and improve the structural properties of biochar and the effect of adsorbing pollutants. This technology can be used to achieve efficient removal of Alternaria toxins and efficient repair of polluted environments.
[0034] 4. The present invention can make the iron-based modified biochar composite material have a good adsorption rate in both 3h and 24h through sodium dodecylbenzene sulfonate. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Thermogravimetric analysis results of rubber seed shells, the raw material for biochar, in Example 1;
[0036] Figure 2 The surface functional group analysis results of the biochar and iron-based modified biochar composites prepared at 450° C. in Example 1;
[0037] Figure 3 The surface functional group analysis results of the biochar and iron-based modified biochar composites prepared at 600°C in Comparative Example 1;
[0038] Figure 4 The X-ray diffraction pattern analysis results of the iron-based modified biochar prepared and modified at 450°C in Example 1;
[0039] Figure 5 This is the X-ray diffraction pattern analysis result of the iron-based modified biochar prepared and modified at 600°C in Comparative Example 1;
[0040] Figure 6 The electron microscopy analysis results of the biochar prepared at 450°C in Example 1;
[0041] Figure 7 The electron microscopy analysis results of the iron-based modified biochar prepared and modified at 450°C in Example 1;
[0042] Figure 8 The electron microscopy analysis results of the biochar prepared at 600°C in Comparative Example 1;
[0043] Fig. 9 The electron microscopy analysis results of the iron-based modified biochar prepared and modified at 600°C in Comparative Example 1;
[0044] Fig.10 This is the energy spectrum of the iron-based modified biochar prepared and modified at 450°C in Example 1;
[0045] Fig.11 This is the energy spectrum of the iron-based modified biochar prepared and modified at 600°C in Comparative Example 1;
[0046] Fig.12 Schematic diagram of the chemical structures of four Alternaria toxins. DETAILED DESCRIPTION
[0047] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] Example 1
[0049] A method for preparing an iron-based modified biochar composite material comprises the following steps:
[0050] (1) Preparation of biochar (BC): Rubber seed shells were crushed after impurities were removed, placed in a ceramic crucible, covered with a lid, and pyrolyzed and carbonized in a muffle furnace. The heating rate was set at 8 °C / min, and the temperature was raised to 200 °C, kept at this temperature for 1 h, and then raised to 450 °C at a rate of 17 °C / min, kept at this temperature for 2 h, cooled, and ground through a 20-mesh sieve to obtain biochar;
[0051] (2) Nano-zero-valent iron modified biochar (nZVI-BC): 24.88 g FeSO4·6H2O and 10 g biochar were added to 200 mL ethanol-water solution, and 0.15 g surfactant was added. The surfactant was sodium dodecylbenzene sulfonate. After ultrasonic treatment for 40 min, nitrogen was introduced to remove dissolved oxygen. The mixture was reacted in a constant temperature oscillator at 26 °C and 150 rpm for 24-26 h. After the reaction, 20 mL of 1 mol / L NaBH4 solution was added at a flow rate of 1.5 mL / min using a peristaltic pump and stirred for 30 min. The solid was centrifuged to obtain a solid, which was washed three times with ethanol and then washed three times with water. The solid was vacuum dried for 12 h to obtain an iron-based modified biochar composite material.
[0052] Comparative Example 1
[0053] The difference between this embodiment and embodiment 1 is that the heating rate is set at 8°C / min, the temperature is raised to 200°C, and kept at this temperature for 1 hour, and then the temperature is raised to 600°C at a rate of 17°C / min, and kept at this temperature for 2 hours.
[0054] Comparative Example 2
[0055] The difference between this comparative example and Example 1 is that the heating rate is set at 20°C / min, the temperature is raised to 200°C, and kept at this temperature for 1.5 hours, and then the temperature is raised to 450°C at a rate of 10°C / min, and kept at this temperature for 1.5 hours.
[0056] Comparative Example 3
[0057] The difference between this embodiment and embodiment 1 is that the surfactant is Triton X-100 (TX-100).
[0058] Comparative Example 4
[0059] The difference between this embodiment and embodiment 1 is that the surfactant is cetyltrimethylammonium bromide (CTAB).
[0060] Comparative Example 5
[0061] The difference between this embodiment and embodiment 1 is that no surfactant is added.
[0062] Performance Testing
[0063] The iron-based modified biochar composite materials prepared in Example 1 and Comparative Examples 1-5 were used as samples for performance testing.
[0064] The adsorbed drugs were alternariol (AOH), alternariol monomethylether (AME), tenuazonic acid (TeA), and tentoxin (TEN). Three parallel experiments were performed in each group.
[0065] Weigh 20 mg of sample in a 15 mL centrifuge tube, add appropriate amount of AOH, AME, TEA, TEN standard working solution in 5 mL of water, so that the final mixed standard solution concentration is 100 ng / mL, oscillate at 180 r / min for 3 h in a constant temperature oscillator at 25 ° C, centrifuge at 12000 r / min for 10 min, take the supernatant and pass it through a 0.22 μm microporous membrane, and use ultra-high performance liquid chromatography-tandem mass spectrometry to determine the adsorption rate (%). When the adsorption rate is less than 1%, it is considered as no adsorption. The results are shown in Table 1. The adsorption rate calculation formula is:
[0066]
[0067] in:
[0068] C0: initial concentration of mixed standard solution (mg / L);
[0069] C e : Concentration when adsorption reaches equilibrium (mg / L)
[0070] Table 1 Adsorption performance test results
[0071]
[0072] It can be seen from Table 1 that the iron-based modified biochar composite material prepared in Example 1 has a good adsorption effect on the four Alternaria toxins. It can be seen from Comparative Example 1 that the adsorption rates of AOH, AME, TeA and TEN prepared by nZVI modification and non-nZVI modification at two temperatures of 450°C and 600°C are different. On the whole, the adsorption rate of the nZVI-BC group is higher than that of the BC group, which indicates that nZVI modification promotes the adsorption capacity of biochar and improves the adsorption rate of the four Alternaria toxins. At the same time, it was found that the adsorption rate of the biochar prepared at 450°C, whether modified or not, was greater than that of the biochar prepared at 600°C. When the pyrolysis temperature was increased from 450°C to 600°C, the number of hydroxyl groups on the surface of the biochar was greatly reduced, and the adsorption capacity decreased, resulting in a decrease in the adsorption rate of the four Alternaria toxins. It can be seen from Comparative Example 2 that the adsorption effect of the iron-based modified biochar composite material decreased by changing the heating rate during the carbonization process. It can be seen from Comparative Examples 3-5 that without adding a surfactant or changing the type of surfactant, the adsorption rate of the iron-based modified biochar composite material decreases to varying degrees.
[0073] Through the adsorption rate of four kinds of Alternaria toxins, it was found that the adsorption rate of AOH and AME by the same biochar material was much higher than that of TeA and TEN. The adsorption rate of AOH and AME could reach more than 80%, while the adsorption rate of TeA and TEN was only about 40% and 7% respectively. The unmodified biochar had no adsorption on TeA and TEN. The reason for the difference in adsorption of AOH, AME, TeA and TEN may be that AOH and AME are both dibenzopyrone derivatives, and their chemical structures are rich in unstable functional groups such as hydroxyl groups and ether bonds, which are easy to combine with functional groups in biochar and then be fixed. TeA and TEN are four amino acid derivatives and cyclic tetrapeptides, respectively. The structures are different from AOH and AME, and the final adsorption effect will also be very different. The data once again proves that the biochar material in the present invention has class specificity in the adsorption of AOH and AME.
[0074] pass Figure 1 It can be seen that the positions of the infrared characteristic peaks of biochar before and after modification are basically the same, but the peak intensities are different. Figure 2-3 It can be seen that after nZVI modification, the contents of carbonyl and ether increased. Fe-O functional groups were observed after modification. 0 The appearance of characteristic peaks indicates that nZVI is successfully loaded on the surface of biochar. The Fe-O functional groups in nZVI can complex with functional groups such as hydroxyl groups in Alternaria toxin, further improving the adsorption and removal effect of rubber seed shell charcoal on Alternaria toxin.
[0075] Figure 2 , Figure 3It can be seen that when the pyrolysis temperature increases from 450℃ to 600℃, the number of hydroxyl groups on the biochar surface is greatly reduced; the positions of the infrared characteristic peaks of biochar before and after modification are basically the same, but the peak intensities are different; after nZVI modification, the contents of carbonyl and ether both increase, and Fe-O functional groups are observed after modification. Figure 4 , Figure 5 From the X-ray diffraction pattern, it can be seen that nZVI is successfully loaded on the biochar surface; Figures 6 to 9 It can be seen that the rubber seed shell biochar becomes fragmented with a smooth surface after high-temperature carbonization; when nZVI is loaded on the surface of the biochar, fine granular substances appear on the surface of the biochar; Fig.10 , Fig.11 It can be seen that the spherical particles containing iron are randomly distributed on the surface of biochar;
[0076] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an iron-based modified biochar composite material, characterized in that: The following steps are involved: (1) preparing biochar: removing impurities from rubber seed shells and crushing them, pyrolyzing and carbonizing them in a muffle furnace, setting the heating rate to 5-10°C / min, heating to 200-210°C, keeping the temperature for 1-2h, then heating to 440-460°C at a rate of 15-20°C / min, keeping the temperature for 2-3h, cooling, grinding and passing through a 20-mesh sieve to obtain biochar; (2) Preparation of nano-zero-valent iron modified biochar: FeSO4·6H2O and biochar were added to an ethanol aqueous solution to obtain a mixture, a surfactant was added, and after ultrasonic treatment for 30-50 min, nitrogen was introduced to blow off the dissolved oxygen, and the mixture was reacted in a constant temperature oscillator at 25-27°C and 140-160 rpm for 24-26 h. After the reaction, NaBH4 aqueous solution was added and stirred for 30-40 min. The mixture was centrifuged to obtain a solid, which was washed and vacuum dried to obtain an iron-based modified biochar composite material.
2. The method for preparing the iron-based modified biochar composite material according to claim 1, characterized in that: The volume ratio of ethanol to water in the ethanol aqueous solution is 1:(2-4).
3. The method for preparing the iron-based modified biochar composite material according to claim 1, characterized in that: The surfactant is sodium dodecylbenzene sulfonate.
4. The method for preparing the iron-based modified biochar composite material according to claim 1, characterized in that: The weight ratio of FeSO4·6H2O and biochar is (23-26):
10.
5. The method for preparing the iron-based modified biochar composite material according to claim 1, characterized in that: The amount of ethanol aqueous solution added is 8-10 times the total weight of FeSO4·6H2O and biochar.
6. The method for preparing the iron-based modified biochar composite material according to claim 1, characterized in that: The temperature was raised to 450°C at a rate of 17°C / min.
7. The method for preparing the iron-based modified biochar composite material according to claim 1, characterized in that: The surfactant is present in an amount of 0.05-0.06% by weight of the mixture.
8. An iron-based modified biochar composite material obtained by the preparation method according to any one of claims 1 to 7.
9. Use of an iron-based modified biochar composite material prepared by the preparation method according to any one of claims 1 to 7 in the adsorption of Alternaria toxin.
10. The use of the iron-based modified biochar composite material in adsorbing Alternaria toxin according to claim 9, characterized in that: The Alternaria toxins include one or more of alternaria toxin, alternaria toxin monomethyl ether, tenuisporic acid, and tenigelnic acid.